2011
DOI: 10.3109/17453674.2011.570672
|View full text |Cite
|
Sign up to set email alerts
|

Failure of total knee arthroplasty with or without patella resurfacing

Abstract: Background and purposePatella resurfacing during primary total knee arthroplasty (TKA) is disputed and new prosthesis designs have been introduced without documentation of their survival. We assessed the impact on prosthesis survival of patella resurfacing and of prosthesis brand, based on data from the Norwegian Arthroplasty Register.Patients and methods5 prosthesis brands in common use with and without patella resurfacing from 1994 through 2009 were included n = 11,887. The median follow-up times were 9 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Higher revisions rates with nonresurfaced patellas as seen in our study have been demonstrated by other authors as well 27,28,35 . Lygre et al found a higher revision rate in arthroplasties, although the finding was not significant.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…Higher revisions rates with nonresurfaced patellas as seen in our study have been demonstrated by other authors as well 27,28,35 . Lygre et al found a higher revision rate in arthroplasties, although the finding was not significant.…”
supporting
confidence: 76%
“…Evidence from the study by Abdel et al indicates that this may not be important 11 . Significant differences in the surgical technique have been brought to light through this analysis 27,28,33 . Some registries contained relatively few posterior-stabilized procedures.…”
mentioning
confidence: 99%
See 3 more Smart Citations